The impact of carbon emission disclosure, ESG, and gender diversity on financial performance in oil and gas industry - Putri, Areta Wahana; Purnama, Ida Ayu (Proceeding International Conference on Accounting and Finance, 2026)
This study examines the impact of carbon emission disclosure, Environmental, Social, and Governance (ESG) performance, and gender diversity on the financial performance of oil and gas companies in Malaysia and Indonesia. The sector was chosen due to its high-carbon nature and strategic economic role in both countries. Data were collected from companies listed on Bursa Malaysia and the Indonesia Stock Exchange for 2022–2024. Multiple linear regression analysis was used to assess the relationships among the variables. The results indicate that collectively, carbon emission disclosure, ESG performance, and gender diversity significantly affect financial performance. Individually, carbon emission disclosure positively impacts financial performance, suggesting that transparency in environmental reporting enhances credibility and investor confidence. Conversely, ESG performance negatively affects short-term profitability, reflecting the costs of implementing sustainable practices. Gender diversity shows no significant effect, indicating limited immediate financial contribution. These findings provide empirical evidence from the oil and gas sector in Malaysia and Indonesia, where sustainability and inclusivity efforts are evolving. The study highlights that transparency and responsible governance have not yet translated into clear financial gains but are essential steps toward aligning with global sustainability standards and supporting long-term economic advantages.